The shape of spectral lines of two-electron Rydberg atoms/ions: analytical solution. (4th May 2017) - Oks, E
Abstract: We consider an isolated two-electron Rydberg atom/ion, where the average distance of the inner electron from the nucleus is much smaller than the average distance of the outer Rydberg electron from the nucleus. We calculate analytically the shape of any spectral line emitted by the inner electron under the rotating electric field of the outer electron—by using the O4 symmetry of hydrogenic atoms/ions. By applying the obtained analytical expressions to the example of the Ly-alpha line, we arrive, in particular, to a peculiar result . Namely, as the spectral line splits into several components, the most intense components exhibit a quadratic Stark effect with respect to the electric field of the outer electron (though it is linear with respect to the dipole moment of the inner electron), while one would intuitively expect a linear dependence on the electric field of the outer electron since the subsystem Z + e is hydrogenic. We provide a physical explanation of this peculiar result.